Thin Film Transistor Amplifiers on Cellulose Acetate - Chaudhary, Sneha; Singh, Subhash; Parameswaran, Chithra; Sambandan, Sanjiv (IEEE journal on flexible electronics, 2025)
With rising environmental concerns, the reduction of electronic wastes to enable sustainable living has become important. A rapidly growing section of the semiconductor industry is flexible electronics which largely relies on the development of thin film transistors (TFTs), light-emitting diodes, solar cells, etc. on plastic substrates. With the deposition of these thin film being additive, the largest volume and weight percentage of the device is the substrate itself. Therefore, a substrate based on nonbiodegradable long-chain polymers is not a tenable choice with regard to sustainability. In this work, we demonstrate the development of TFT circuits on cellulose acetate substrates with the degree of substitution of the acetyl group on cellulose being 2.4. The key novelties of this work are the development of TFTs with 40% yield and the demonstration of small signal amplifiers on flexible sheets of cellulose acetate without the use of a planarization layer. The absence of a planarization layer, which is typically nonbiodegradable, removes the significant pollutant thereby making the eventual device largely biodegradable. It is shown that the TFTs obtained with and without the basement layer are not too different in performance. While the acetyl group on cellulose is understood to slow down the degradation, our demonstrations corroborate with other studies and demonstrate its degradation in soil.